2013
DOI: 10.1021/ol400625f
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantiospecific Platinum-Catalyzed Cycloisomerizations: Synthesis of Enantioenriched Oxabicycloheptene Derivatives

Abstract: Enantiospecific cycloisomerizations of 1,6-enynes to form oxabicyclo[4.1.0]heptene derivatives are described. Enantiospecificity is consistently high regardless of alkene or alkyne substitution, providing a general approach to greatly enantioenriched cyclopropanes. Additionally, a model for stereochemical transfer is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…We, therefore, resorted to transition‐metal chemistry to effect ring opening in a C−C bond activation process . Tipper reported in 1955 that cyclopropane reacts with platinum(II) chloride to give a complex subsequently shown to contain a platinacyclobutane . Several groups have shown that, when the cyclopropane is substituted with an alcohol or ether group, the platinacyclobutane is unstable and undergoes ring opening .…”
Section: Resultsmentioning
confidence: 99%
“…We, therefore, resorted to transition‐metal chemistry to effect ring opening in a C−C bond activation process . Tipper reported in 1955 that cyclopropane reacts with platinum(II) chloride to give a complex subsequently shown to contain a platinacyclobutane . Several groups have shown that, when the cyclopropane is substituted with an alcohol or ether group, the platinacyclobutane is unstable and undergoes ring opening .…”
Section: Resultsmentioning
confidence: 99%
“…[26] In this case, a control reaction showed that the linear substrate 1 a remained unchanged in the presence of AgBF 4 alone at ambient tempera-ture (Table 2, entry 7), that is, any background racemic process due to the silver salt can be categorically ruled out. Subsequently, by using the L11-ligated complex, the cycloisomerisations of three other substrates 1 b-d were performed in the presence of various amounts of silver salt, with the stoichiometric ratio of Au/Ag either 1:1 or 2:1 ( Table 2, entries [8][9][10][11][12]. In each case, the product yield was lower when silver salt (0.5 equiv) was employed but the level of enantioselectivity remained invariant.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] The reaction was first discovered in 1995 by Blum and coworkers by using a catalytic amount of PtCl 4 . [8] Since then, a number of other p-acidic transition-metal catalysts were reported, including Rh, [9,10] Ir, [11] Pt [12][13][14] and Au catalysts. [15,16] The first enantioselective examples were provided by Michelet and co-workers in 2009, by using a gold(I) complex of the chiral diphosphine ligand L1 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric gold-catalyzed cycloisomerization of nitrogen-bridged as well as oxygen-bridged 1,6-enynes 188 Very recently, Newcombe and Ferreira reported an enantiospecific cycloisomerization starting from enantioenriched allyl propargyl ethers (Scheme 85). 189 The enantiospecificity of the reaction ranged from 80 to >99%, calculated as the percentage of the product's enantiomeric excess over that of the starting ether. The stereochemistry of the product was confirmed by X-ray structural analysis and the optical rotation values were positive.…”
Section: Scheme 84mentioning
confidence: 99%